Phenotypic characterization of amoeboid forms of trichomonas vaginalis / Kasthuri A/P Jewarethnam - Jewarethnam, Kasthuri (2014)

(untitled)
Trichomonas vaginalisis a flagellated protozoan parasite that causes significant health drawbacks to humans, predominantly in women by causing a non-viral sexually transmitted disease known as trichomoniasis. Different morphological properties of T. vaginalis were recognized as the key for infections in humans with trophozoites and pseudocysts as the two notable forms. Recently, amoeboid form was identified in suspension cultures and was reported as an integral life cycle of T. vaginalis. The present study was conducted to study the phenotypic characteristics of amoeboid forms in suspension culture i.e. growth profile, evaluating factors that trigger formation of this shape, staining characteristics and transformational changes to amoeboid forms. The study showed that out of nine symptomatic isolates consisting of six cervical neoplasia (CN) and three non-cervical neoplasia (NCN), only the CN isolates showed viable amoeboid forms. Amoeboid forms were distinguished based on morphological properties such as formation of pseudopodia-like cytoplasmic extensions, non-motile, none or inactive flagella, flattened, larger in size with abnormal shapes and presence of more inclusion-like bodies. Growth profile of amoeboid forms showed an initial formation in the culture on day one itself with significantly optimal count on day three cultures with total mean average of 3.22 ± 0.11 x 104 T. vaginalis/ml (p < 0.05) for all CN isolates (CN1 – CN6) and none in NCN isolates (NCN2 – NCN4). This was mainly attributed to the virulence and high proliferation rate of T. vaginalis in CN isolates compared to NCN isolates. The study also confirmed a significant formation of amoeboid forms in suspension cultures of CN isolates (CN1 – CN6) under the three growth parameters tested. Firstly, optimum amoeboid forms were observed on day 3 when the growth media were overcrowded with parasites with mean average of 9.88 ± 0.50 x 105 T. vaginalis/ml (p < 0.05). Increased concentration of horse iv serum (15 %) also observed a significant development of amoeboid forms with mean average of 9.95 ± 0.47 x 104 T. vaginalis/ml (p < 0.05). The third parameter on the effect of metronidazole drug (0.0001 mg/ml) reported optimal amoeboid forms with mean average of 3.61 ± 0.06 x 104 T. vaginalis/ml (p < 0.05). The study for the first time introduced Modified Field’s stains as a rapid detection method (15 seconds) compared to Giemsa stain. The staining provided better and sharper contrast which differentiated the nucleus and cytoplasm. The staining showed amoeboid forms to have irregular shapes, rough surfaces and with single or multi-nucleated. Using light microscopy, different morphological changes based on size and shapes were observed as the trophozoites of T. vaginalis transformed into amoeboid forms. The amoeboid forms measured approximately 25 μm to 27.5 μm in length and 20 μm to 22.5 μm in width and were seen predominantly in cultures after 48 hours culture. The study opened new prospects for further research to understand better the role of amoeboid forms of T. vaginalis in contributing to the pathogenesis and development of cervical cancer in women.